Pengaruh Inflasi dan Pendapatan Perkapita terhadap Konsumsi Rumah Tangga di Provinsi Aceh - Fanny Nailufar; Miftahul Jannah; Reza Juanda (Universitas Teuku Umar, 2022)
This study examined and analyzed the influence of inflation rate and per capita income on household consumption in Aceh province. This study used secondary data accessed on the Central Bureau of Statistics for 12 years (2009-2020). The method of data analysis used was the Multiple Linear Regression analysis method using Eviews 10. The results study indicated that inflation had no significant effect on Household Consumption in Aceh Province, and Per capita income had a positive and significant effect on Household Consumption in Aceh Province. Simultaneously, Inflation and Per capita Income had a significant effect on Household Consumption in Aceh Province